Pentingnya Pendidikan Ekonomi Informal Dalam Mewujudkan Perilaku Ekonomi Mahasiswa Yang Rasional - Inanna, Inanna (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2020)
This study aims to determine the effect of education provided by parents in realizing rational economic behavior of students. The method used is a quantitative approach with a population of 659 students and a sample of 70 students. Data collection techniques used were observation, questionnaires and documentation. The data analysis technique used is simple linear regression analysis. The results showed that informal economic education had an influence in realizing rational economic behavior in the students of economic education in Makassar State University